A review of available hybrid renewable energy systems in Malaysia - Nur Huda. M Tambi; Hadi Nabipour Afrouzi; Kamyar Mehranzamir; Jubaer Ahmed (Institute of Advanced Engineering and Science, 2020)
The utilization of conventional sources of energy releases harmful pollutants to the environment causing global warming and acid rain. For that reason, it becomes necessary to use a non-depletable, sustainable and eco-friendly renewable energy as a mean of producing electricity. Malaysia is tropical country rich in resources beneficial in electricity generation as it is in equatorial region therefore it has an abundance of solar irradiance of average annually. In addition, Malaysia’s demand in electricity is increasing to 124,677 GWh by 2020. Therefore, the electricity generation from renewable sources in Malaysia is anticipated to grow in the future alongside the government endorsement due to its clean, eco-friendly and free source of energy which can highly reduce the dependency on oil and gas that emits harmful pollutants to the environment. This paper gives a comprehensive review on the renewable projects and researches in Malaysia, challenges that affect popularity of renewable energy in Malaysia and available and successful renewable energy system in Malaysia.